PARADIGMA TRADISIONALIS DALAM PEMIKIRAN POLITIK ISLAM MODERN - Efi Syarifudin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2006)
As a traditionalist political thinker in modern era, Rasyid Ridha (1865-1935) had shown a relation between caliphate system and modern Islamic state system. He tried to formulate ''tradition